Fertilizers - a benefit or a hazard to agriculture? - Olembo, R. J. (Technical Centre for Agricultural and Rural Cooperation, 1990)
R J Olembo Professor R J Olembo Is a Kenyan geneticist currently serving at the United Nations Environment Programme as Deputy Assistant Executive Director. Before joining UNEP, he held academic positions at Makerere University, Uganda and the...